Skulduggery Pleasant - Landy, Derek (New York : HarperCollins, 2007)
When twelve-year-old Stephanie inherits her weird uncle's estate, she must join forces with Skulduggery Pleasant, a skeleton mage, to save the world from the Faceless Ones.
Keywords: Magic -- Fiction; Fantasy